2010
DOI: 10.1111/j.1440-1800.2009.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

The textual organization of placement into long‐term care: issues for older adults with mental illness

Abstract: Arranging placement of older adults from hospital mental health units into nursing homes or assisted living facilities can be difficult and protracted. The difficulty in placing these individuals is often attributed to stigma; that is, personnel in nursing homes are reluctant to accept mentally ill older adults because of the fear of mental illness and violence. Using an institutional ethnographic approach, we argue the importance of exploring how nursing home access is organized, especially the institutional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 27 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…, Lane et al . ) have all been postulated as reasons that prevent older adults with MI from getting the needed assessment, diagnoses and treatment they require to stay well. As a result, these delays increased hospital LOS, and the inherent increased use of resources, for older adults with MI diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Lane et al . ) have all been postulated as reasons that prevent older adults with MI from getting the needed assessment, diagnoses and treatment they require to stay well. As a result, these delays increased hospital LOS, and the inherent increased use of resources, for older adults with MI diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in-hospital processes and political bureaucracies are also suspected of being at play in increasing the resource use of older adults with MIs. Lack of or inappropriate referrals (Wen et al 2007, Hammond et al 2009, Fernando et al 2010, test delays (Hammond et al 2009), lack of home care and community services (Kozyrskyj et al 2004, Menec et al 2004, Mackenzie et al 2006), inefficient discharge processes (Hammond et al 2009, Popejoy 2011, inefficient medical management (Brownell & Roos 1995, Butler et al 1996, Guijarro et al 2010) and organizational politics (Rogers & Barusch 2000, Silverstein et al 2008, Lane et al 2010) have all been postulated as reasons that prevent older adults with MI from getting the needed assessment, diagnoses and treatment they require to stay well. As a result, these delays increased hospital LOS, and the inherent increased use of resources, for older adults with MI diagnoses.…”
Section: Figurementioning
confidence: 99%
“…Lane and colleagues (2010), examining how ALs decide whether to admit persons with SMI, reported that dangerous or problematic behaviors, a concern shared for some applicants with dementia, often resulted in an AL’s rejection of mentally ill applicants. A multi-state AL sample found 34% of residents evidencing one or more challenging behaviors due to mental illness, dementia or both (Gruber-Baldini, Boustani, Sloane & Zimmerman, 2004).…”
Section: Mental Illness In Assisted Livingmentioning
confidence: 99%
“…Some states have regulations for care of persons with SMI in AL, but concerns remain regarding the implementation and quality of these services (Becker et al, 2002; Lane et al, 2010). This gap is especially troubling, considering that AL settings are not legally required to identify, treat, or refer persons with mental health issues to appropriate, specialized services (Hudson et al, 2013).…”
Section: Mental Illness In Assisted Livingmentioning
confidence: 99%
“…The institutional ethnographic work of Lane et al . (2010) and Lane (2011) supports our challenge of taken‐for‐granted practices that quantify maths competency in nursing education and that use an established set of ideological practices to turn those numerical quantifications into a measure of ‘patient safety’.…”
Section: Maths For Medications: Disrupting the Discoursementioning
confidence: 99%